MENINGKATKAN KUALITAS SDM PROGRAM BAHASA ARAB BERLANDASKAN TEORI MANAJEMEN FREDERICK WINSLOW TAYLOR: indonesia - Abdul Latif; Hasanuddin; Ahksan; Nuril Mufidah (Fakultas Tarbiyah Universitas Ibrahimy, 2024)
This research aims to explore more data regarding: (1) how is HR competency developed? (2) how is employee recruitment and training? (3) How is employee performance monitored? (4) How is the cooperation between management and employees? With a research focus on Arabic language program management. The theory used to analyze is the scientific management theory initiated by Frederick Winslow Taylor. This research uses a case study research method. This case study research was carried out at Ar-Rahmah Tahfidz Islamic Boarding School Malang in the 2023/2024 academic year, focusing on the Arabic language program in the dormitory. The researcher concluded that implementing Arabic language program management at Ar-Rahmah Tahfidz Islamic Boarding School Malang was by the principles of scientific management initiated by Frederick Winslow Taylor. This is illustrated through the following points. First, developing the quality of human resources through training to improve the quality of Arabic language knowledge and skills for dormitory companions. Second, employees are selected using outsourcing to fill positions in the Arabic language driving division called Muharrik lughoh Arabiyah (Arabic language driving). Third, manajer supervise three types of care: feedforward, current control, and feedback control. Fourth, distribute tasks proportionally.